The jumbled jigsaw : an insider's approach to the treatment of autistic spectrum 'fruit salads' - Williams, Donna, 1963- (Jessica Kingsley Publishers, 2006)
This book exposes autism spectrum disorders as a combination of a whole range of often underlying conditions. Exploring everything from mood, anxiety, obsessive-compulsive and tic disorders to information processing and sensory perceptual difficulties and more, Donna demonstrates how such conditions can combine to form a 'cluster condition'.